Combined use of endosonography and endoscopic retrograde cholangiopancreatography in the same session - Belkıs Ünsal; Emrah Alper; Behlül BAYDAR; Fatih Aslan; Zehra Akpınar; Zafer BUYRAÇ; Mehmet Kadir AKSÖZ (Turkish Journal of Gastroenterology, 2019)
-